Outcome measures in ANCA-associated vasculitis. - Suppiah, R; Robson, J; Luqmani, R (2010)
The outcome in patients with antineutrophil cytoplasm antibody (ANCA)-associated vasculitis has considerably improved with the use of potent immunosuppression. In the most severe cases, mortality remains an important risk despite aggressive intervention. However, for most patients who survive, quality of survival is affected by morbidity due to low-grade disease activity, episodes of relapse, damage from the effects of disease and its treatment, development of associated comorbidity, and the social and psychological problems of chronic disease. A rational approach to management of patients with ANCA-associated vasculitis requires careful measurement of these different facets of disease, so that treatment is appropriate. This article reviews the development of assessment tools used to quantify disease in vasculitis, which have been extensively used in clinical trials and are also appropriate for use in individual patient care.